Mammalian homologues of the Polycomb-group gene Enhancer of zeste mediate gene silencing in Drosophila heterochromatin and at S. cerevisiae telomeres. - Laible, G (1997)
Gene silencing is required to stably maintain distinct patterns of gene expression during eukaryotic development and has been correlated with the induction of chromatin domains that restrict gene activity. We describe the isolation of human (EZH2) and mouse (Ezh1) homologues of the Drosophila Polycomb-group (Pc-G) gene Enhancer of zeste [E(z)], a crucial regulator of homeotic gene expression implicated in the assembly of repressive protein complexes in chromatin. Mammalian homologues of E(z) are encoded by two distinct loci in mouse and man, and the two murine Ezh genes display complementary expression profiles during mouse development. The E(z) gene family reveals a striking functional conservation in mediating gene repression in eukaryotic chromatin: extra gene copies of human EZH2 or Drosophila E(z) in transgenic flies enhance position effect variegation of the heterochromatin-associated white gene, and expression of either human EZH2 or murine Ezh1 restores gene repression in Saccharomyces cerevisiae mutants that are impaired in telomeric silencing. Together, these data provide a functional link between Pc-G-dependent gene repression and inactive chromatin domains, and indicate that silencing mechanism(s) may be broadly conserved in eukaryotes.